The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1002/ijc.24245
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin subclass levels in patients with non‐Hodgkin lymphoma

Abstract: Allergy/atopy has been suggested to protect against non-Hodgkin lymphoma (NHL) and specific IgE levels are decreased in patients with NHL. We speculated that all immunoglobulin subclass levels might be downregulated in NHL and examined levels of IgM, IgD, IgA, IgE, IgG and IgG 4 in 200 NHL patients and 200 age-and sexmatched controls. Patients with B-cell NHL of many types had consistently lower median immunoglobulin subclass levels than controls. In every subclass except IgD, about 10-15% of B-cell NHL patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
1
21
2
Order By: Relevance
“…The incidence of IgA, IgG, or both IgA and IgG hypogammaglobulinemia in this series of 207 untreated WM patients was 63.3%, 58.0% and 49.3%, respectively, which is similar to the incidence reported among patients with chronic lymphocytic leukemia, 6,7 but higher than that reported in other indolent lymphomas in which the incidence of IgA and IgG hypogammaglobulinemia ranges from 10-20%. 7 The incidence of IgA and/or IgG hypogammaglobulinemia observed in this study also appears to be higher than that observed in individuals with IgM monoclonal gammopathy of unknown significance (MGUS), although there is great variation in the reported incidences in this latter conidtion (8-35%). 15,16 The inclusion of patients with up to 10% bone marrow disease involvement, who are now considered to have WM based on consensus diagnostic criteria, may account for the higher incidence of IgA and/or IgG hypogammaglobulinemia observed in the series reported by Kyle et The presence of IgA and/or IgG hypogammaglobulinemia was reported to predict for evolution of IgM MGUS to WM in the series of patients studied by Kyle et al 16 While the presence of IgA and IgG hypogammaglobulinemia per se was not associated with disease progression, WM patients in this series who were initially managed with a 'watch and wait' strategy but whose disease ultimately progressed had lower median IgA and IgG levels.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The incidence of IgA, IgG, or both IgA and IgG hypogammaglobulinemia in this series of 207 untreated WM patients was 63.3%, 58.0% and 49.3%, respectively, which is similar to the incidence reported among patients with chronic lymphocytic leukemia, 6,7 but higher than that reported in other indolent lymphomas in which the incidence of IgA and IgG hypogammaglobulinemia ranges from 10-20%. 7 The incidence of IgA and/or IgG hypogammaglobulinemia observed in this study also appears to be higher than that observed in individuals with IgM monoclonal gammopathy of unknown significance (MGUS), although there is great variation in the reported incidences in this latter conidtion (8-35%). 15,16 The inclusion of patients with up to 10% bone marrow disease involvement, who are now considered to have WM based on consensus diagnostic criteria, may account for the higher incidence of IgA and/or IgG hypogammaglobulinemia observed in the series reported by Kyle et The presence of IgA and/or IgG hypogammaglobulinemia was reported to predict for evolution of IgM MGUS to WM in the series of patients studied by Kyle et al 16 While the presence of IgA and IgG hypogammaglobulinemia per se was not associated with disease progression, WM patients in this series who were initially managed with a 'watch and wait' strategy but whose disease ultimately progressed had lower median IgA and IgG levels.…”
Section: Discussioncontrasting
confidence: 48%
“…5 The presence of hypogammaglobulinemia of the 'uninvolved' immunoglobulin has also been reported among other B-cell malignancies. 6,7 The etiology of this finding remains unclear, but has been speculated to be based on tumor-induced immunoparesis and host-mediated homeostatic regulation of 'uninvolved' immunoglobulin production.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] The inverse association between IgE production levels and risk for developing diseases, such as leukemia, lymphoma, glioma, pancreatic cancer, among others, has been extensively evaluated. [48][49][50][51][52][53] Jensem-Jarolin et al 45 showed that, in conditions where serum IgE are directed against tumor-associated antigens, these immunoglobulins could be considered as mediators of cell-cell contact where the tumor cell would be recognized by the immune effector cell resulting in an immune synapse known as antibody-dependent cytotoxicity (ADCC).…”
mentioning
confidence: 99%
“…32,33 IgG levels were not decreased in one study, 32 but in contrast, it was decreased in other studies, 33 while a study 34 showed no increase in IgG levels, and lower IgG levels in NHL patients was observed. 33,34 Levels of all immunoglobulin class were decreased in NHL patients. Another study which supports our results demonstrated that the most frequent hypoimmunoglobulinaemia is in class IgM (22%), followed by IgA (8%).…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresismentioning
confidence: 71%
“…Another study which supports our results demonstrated that the most frequent hypoimmunoglobulinaemia is in class IgM (22%), followed by IgA (8%). 35,36 In NHL patients intrinsic B-cell defects, increased T-cell or monocyte suppressor activity, and diminished T-helper activity m a y a l s o c o n t r i b u t e t o t h e hypogammaglobulinaemia. [37][38][39] One of ten studied patients with NHL had an M band, this has been reported by other worker.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresismentioning
confidence: 99%